Healthy Lifestyle Behaviour Changes During the Covid-19 Pandemic in Youth and Adult Groups in Indonesia - Fillah Fithra Dieny; Firdananda Fikri Jauharany; A.Fahmy Arif Tsani; Choirun Nissa (Universitas Aisyah Pringsewu, 2022)
The Covid-19 pandemic has changed various kinds of human behavior, especially behavior related to health. Health institutions have issued protocols to prevent the virus so that it affects people's lifestyles a lot. This study aims to analyze changes in people's behavior, especially healthy lifestyles before and during the Covid-19 pandemic in Indonesia. A cross-sectional study that involved 563 subjects. The inclusion criteria are that the subject lives in Indonesia, aged 12-55 years, is willing to take part in the research and fill out an online questionnaire. The independent variable is the time that is divided into before and during the Covid-19 pandemic. The dependent variable is healthy lifestyle behavior which includes hand washing habits, exercise habits, weight checking habits, sunbathing habits and smoking habits. The analysis includes univariate analysis, normality test and bivariate analysis using the Wilcoxon test to analyze differences in healthy lifestyle behavior before and during the Covid-19 pandemic. The results showed that 425 subjects (75.5%) were female, and more than 50% of subjects had a bachelor's level education and above. Most of the subjects live in urban areas (69.1%), come from the island of Java (86.0%), have daily activities not related to health (58.1%) and carry out government recommendations, namely stay at home (76.4%). There were differences in hand washing frequency (p less than 0.001), exercise frequency (p=0.037), sunbathing frequency (p less than 0.001), and sunbathing duration (p less than 0.001) between before the pandemic compared to during the Covid-19 pandemic. However, there was no change in smoking habits based on the number of cigarettes before and during the Covid-19 pandemic. The conclusion of the research that during the Covid-19 pandemic, public awareness to have a clean and healthy lifestyle, namely increasing the frequency of washing hands, doing sports and sunbathing.Abstrak: Pandemi Covid-19 telah merubah berbagai macam perilaku manusia, khususnya perilaku yang terkait dengan kesehatan. Lembaga kesehatan telah mengeluarkan protokol pencegahan virus tersebut sehingga banyak mempengaruhi gaya hidup masyarakat. Penelitian ini bertujuan untuk menganalisis perubahan perilaku masyarakat khususnya perilaku gaya hidup sehat (healthy lifestyle) sebelum dan saat terjadi pandemi Covid-19 di Indonesia. Penelitian dengan design cross-sectional yang dilakukan pada 563 subjek. Kriteria inklusi adalah subjek tinggal di Indonesia, berusia 12-55 tahun, bersedia mengikuti penelitian dan mengisi kuesioner secara online. Variabel bebas adalah waktu yang dibedakan menjadi sebelum dan saat pendemic Covid-19. Variabel terikat perilaku gaya hidup sehat (healthy lifestyle) yang meliputi kebiasaan cuci tangan dengan sabun, kebiasaan olahraga kebiasaan pengecekan berat badan, kebiasaan berjemur dan kebiasaan merokok. Analisis meliputi analisis univariat, uji kenormalan dan analisis bivariat menggunakan uji Wilcoxon untuk menganalisis perbedaan perilaku healthy lifestyle sebelum dan selama pandemi Covid-19. Hasil penelitian menunjukkan bahwa sebanyak 425 seubjek (75,5%) berjenis kelamin perempuan, dan lebih dari 50% subjek memiliki tingkat pendidikan sarjana dan diatasnya. Sebagian besar subjek tinggal di perkotaan (69,1%), berasal dari pulau jawa (86,0%), aktifitas sehari hari tidak berhubungan dengan kesehatan (58,1%) dan melakukan anjuran pemerintah yaitu stay at home (76,4%). Ada perbedaan frekuensi cuci tangan (p kurang dari 0,001), frekuensi olahraga (p=0,037), frekuensi berjemur (p kurang dari 0,001), dan durasi berjemur (p kurang dari 0,001) antara sebelum pandemi dibandingkan dengan selama pandemi Covid-19. Namun tidak ada perubahan pada kebiasaan merokok berdasarkan jumlah batang rokok sebelum dan selama pandemi Covid-19. Simpulan dari penelitian ini adalah masa pandemi Covid-19 meningkatkan kesadaran masyarakat untuk berperilaku hidup bersih dan sehat yaitu meningkatnya frekuensi cuci tangan dengan sabun, melakukan olahraga dan berjemur.